The effect of the self-organized and inquiry-based learning styles on learning the performance of some basic volleyball skills for fifth-grade middle school students (Journal of the College of Basic Education, 2022)
The study aimed to prepare educational exercises and employ them in a self-organized learning method to identify their effect on the performance of some basic skills in volleyball among fifth-grade students, and prepare educational exercises and employ them in a learning method based on the inquiry to identify their impact on the performance of some basic skills in volleyball among fifth-grade students Preparatory, and the researcher adopted the experimental research method by designing the two experimental groups for each group for a specific educational style, for the fifth preparatory class students in the Distinguished Secondary School for Girls within the administrative configurations of The vessels in the Baghdad governorate Almstmrat regular attendance for the academic year (2019/2020) of their number (52) students Okhturn of two divisions at random by (55.914%) To be the two experimental groups (26) students in each of them, and performance evaluation tests were adopted after the video filming of the three skills tests and the application of the two methods by (3) educational units for each skill to continue the application of educational curriculum exercises for each method (9) weeks by one educational unit according to the weekly lessons schedule The concepts of each method were used in the application of educational exercises and the number of times they performed all that they contain in terms of stimulating the role of female learners in the lesson, and checking the results with a system (SPSS-V26) to be the conclusions and applications: My self-organized learning method, based on the inquiry, helps the learners to: Improve their performance of the skills of sending and receiving and blocking the volleyball, and that female learners in a self-organized learning method outperformed their skills over female learners by learning based on inquiry, and it is necessary to increase the capabilities and competencies of physical education teachers in middle schools and enable them to apply methods that increase the activity of female learners and activate their role In the physical education lesson